Yaws' handbook of properties for aqueous systems - Yaws, Carl L. (Knovel, 2012)
"Yaws handbook of properties for aqueous systems features 17 chapters and data tables for water solubility, Henry's law constant, activity coefficient at infinite dilution, octanol-water partition coefficient, and bioconcentration factor for 17,390 organic and 340 inorganic substances: gases and liquids, hydrocarbons, oxygen, nitrogen, sulfur, and halogen organics and Ag to Zn inorganics. The additional interactive table format provides granular search accessibility and the means for comparison of properties across substances. The tables contain chemical names, molecular formulae, and CAS numbers for enhanced searchability. This compilation features measured and calculated data. Regression analysis was applied to data points obtained from reliable published sources to obtain empirical equations that can be used to calculate the properties of organic and inorganic substances within a specific range of temperatures."--Publisher description.
Keywords: Water chemistry -- Tables.; Solution (Chemistry) -- Tables.; Water -- Analysis -- Tables.; Green chemistry -- Handbooks, manuals, etc.; elektronické knihy; electronic books